Delirium Trigger Videos - Jorge Ruiz; Miguel Paniagua; Marcos Milanez; Juan Axel; F Phancao; Aaron McEntire; R Picardo (Association of American Medical Colleges, 2006)
Abstract A trigger video is a short film, generally only a few minutes long, whose aim is to stimulate and provoke learning. Trigger videos have been found to be an excellent stimulus for discussion and particularly effective for analysis of complex issues in health care. Their use can enhance medical education programs by encouraging an active learning process in which learners identify with the situations and problems presented and are motivated to seek an action-oriented solution. Such an approach empowers learners to develop their own answers in a supportive and mutually reinforcing context. The delirium trigger videos here are 1- to 2-minute video clips produced by GeriU, the Online Geriatrics University, at the Stein Gerontological Institute. These videos deliver the information in an interactive way, step by step, through written text, animations, graphics, and video clip demonstrations. Each video contains a visual scenario regarding delirium that learners must address. There is often an emotional appeal to the video. Working in small groups, students view the situation, identify the problem, consider different courses of action, and then make recommendations. One lesson learned from this project was simplicity: These videos were originally part of larger online presentations, but large e-learning modules can overwhelm medical students. A learner should not spend too much time going through lengthy educational tools, especially at the expense of content and interaction.